2002
DOI: 10.1007/s00105-002-0346-8
|View full text |Cite
|
Sign up to set email alerts
|

Purpura fulminans Fatale Folge einer alltäglichen Therapie?

Abstract: A 39-year old man developed purpura fulminans, a manifestation of disseminated intravascular coagulopathy, with rhabdomyolsis following the i.m. injection of diclofenac.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 23 publications
0
5
0
1
Order By: Relevance
“…The first case responded well to high-dose methylprednisolone (3); the second case resolved rapidly after withdrawal of propylthiouracil without using systemic corticosteroids (4). Hengge et al (5) reported a 39-year-old man who developed PF following the intramuscular injection of diclofenac. There are also two reports in the Chinese literatures on PF induced by whitening cosmetics and pesticides in a 20-year-old and a 28-year-oid healthy Chinese woman, respectively (6,7).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The first case responded well to high-dose methylprednisolone (3); the second case resolved rapidly after withdrawal of propylthiouracil without using systemic corticosteroids (4). Hengge et al (5) reported a 39-year-old man who developed PF following the intramuscular injection of diclofenac. There are also two reports in the Chinese literatures on PF induced by whitening cosmetics and pesticides in a 20-year-old and a 28-year-oid healthy Chinese woman, respectively (6,7).…”
Section: Discussionmentioning
confidence: 98%
“…Drug-induced PF may be distinguished from the other three types of PF in following respects: (/) it occurs in patients with a history of administering certain medications; (//) and with no prodromal infections: {Hi) serum protein C atid protein S levels may be normal: (/V) it responds to corticosteroids; (v) generally with a good prognosis (3)(4)(5). Propylthiouracil was reported to induce PF in two patients with Grave's disease (3,4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When spontaneous epithelization fails to occur, surgical therapy is necessary. With deep and extensive damage surgical intervention such as fasciotomy in the presence of compartment syndrome or the amputation of digits are needed [5].…”
Section: Discussionmentioning
confidence: 99%
“…Es gibt auch einen Bericht über eine Purpura fulminans, die nach der Gabe von Diclofenac auftrat, wobei dieses Medikament im Rahmen einer fieberhaften Erkrankung verabreicht wurde, aber kein Erreger nachgewiesen werden konnte [10] Symptomatik Zuerst treten disseminierte Petechien auf, die in kurzer Zeit zu großen Ekchymosen konfluieren (. Abb.…”
Section: Purpura Fulminansunclassified